The risk of board composition on auditor's risk assessment in Nigeria / Salau Abdulmalik Olarinoye and Ayoib Che Ahmad - Abdulmalik Olarinoye, Salau; Che Ahmad, Ayoib (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
This study examines the link between outside directors and audit fees. The study used data from 94 non-financial-listed companies on the Nigerian Stock Exchange from 2008 to 2013. The study used cross-sectional time-series feasible generalized least squares (FGLS) regression, which explains heteroscedasticity and autocorrelation in testing the effect of non-independent non-executive directors and independent non-executive directors on auditor pricing decisions in Nigeria. Our result indicates that the proportion of non-independent non-executive directors on boards has a negative relationship with audit fees, whereas the proportion of independent non-executive directors has a positive relationship with audit fees. Further analysis reveals that block shareholding moderates the effect between outside directors and audit fees. These findings have both policy and practical implications on corporate governance. For instance, future regulatory reforms can consider collaborative board models instead of the insistence on more independent director presence in the boardroom.